(untitled) (Pedagogy of Higher and Secondary Education, 2015)
Makarenko V. V., Spivak V. M. Circuit simulation as a tool to explain the processes occurring in electrical circuits. The article describes a specific example of the use of simulation programs NI Multisim to explain and illustrate the complex processes that occur in electronic devices. The choice of the simulation software for the analysis of the circuit design from the point of view of functionality and the cost of its acquisition is grounded. The promising application of simulation programs in the study of electrical engineering and electronics courses is proved.